2007
DOI: 10.1021/jp0657538
|View full text |Cite
|
Sign up to set email alerts
|

Photoreaction of Ethanol on TiO2(110) Single-Crystal Surface

Abstract: The adsorption, thermal, and UV reactions of ethanol over a TiO 2 (110) single-crystal surface have been studied in the presence and the absence of molecular oxygen. Adsorption of ethanol is dissociative at room temperature and gives rise to two C1s peaks of equal intensities (at 285.2 and 286.5 eV) attributed to -CH 3 and -CH 2 O-groups, respectively. The surface coverage at saturation (of the dissociative adsorption mode at 300 K) is close to 0.5 with respect to Ti atoms. Thermal annealing resulted in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
129
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(141 citation statements)
references
References 68 publications
12
129
0
Order By: Relevance
“…3,4 They have been explored in applications from energy storage to water purification to transparent conductive electrodes. 5,6,7,8 Furthermore, spontaneous intercalation of organic molecules (urea, hydrazine, DMF, etc. ), as well as spontaneous and electrochemical intercalation of various cations (Li , Al 3+ ) were previously reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 They have been explored in applications from energy storage to water purification to transparent conductive electrodes. 5,6,7,8 Furthermore, spontaneous intercalation of organic molecules (urea, hydrazine, DMF, etc. ), as well as spontaneous and electrochemical intercalation of various cations (Li , Al 3+ ) were previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially pertinent now that a number of MXene applications have been explored involving interactions with salt solutions; for example, when MXenes are used in supercapacitors with aqueous electrolytes, 10,13 as sorbents for Pb or Cr ions, 14,15 or membranes for ion sieving, the nature of the cation can play a large role in affecting the sorption efficiency or structure and permeability of the membranes. 6 It has been shown that spontaneous cation intercalation described in reference 10 may lead to changes in MXene surface chemistry, 16 but no systematic studies have been reported. If intercalated cations are structurally inherent in MXenes, controlling their concentrations and understanding their effects on interlayer separation can be crucial for tuning electrochemical energy storage, optical, and ion-exchange properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a lot of surface science techniques have been used to study the fundamental aspects of this important system. For example, the thermal chemistry of ethanol on TiO 2 (110) has been examined by temperature programmed desorption (TPD) [11−13], scanning tunneling microscopy (STM) [14], X-ray photoelectron spectroscopy (XPS) [12,15], * Authors to whom correspondence should be addressed. E-mail: chuanyaozhou@dicp.ac.cn, xmyang@dicp.ac.cn and density functional theory (DFT) calculations [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…E-mail: chuanyaozhou@dicp.ac.cn, xmyang@dicp.ac.cn and density functional theory (DFT) calculations [14,16]. The photoreaction of ethanol on TiO 2 (110) has also been investigated by TPD and XPS techniques [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation